Estimation of direct and maternal covariance of production efficiency traits in Murrah buffalo - Sharma, Smriti; Dhaka, Surender; Patil, Chandrashekhar Santosh; Rathi, pallavi (Indian Journal of Dairy Science, 2024)
The study employed data collected from 662 Murrah buffaloes meticulously documented over a 24-year period (1996-2019). The data were sourced from historical pedigree records maintained at the buffalo farm of the Department of Livestock Production and Management (LPM) at Lala Lajpat Rai University of Veterinary and Animal Sciences in Hisar. The average values under univariate animal model for production efficiency traits viz. MCI and MSC were 4.84 kg/day and 1.33 kg/day, respectively. Six univariate animal models were utilized to compute (co)variance components and heritabilities for traits related to first lactation production efficiency. Among these models, Model 1 was identified as the most suitable for calculating milk yield per day of calving interval (MCI), while Model 2 proved optimal for milk yield per day of age at second calving (MSC). Maternal effects were observed to influence MSC (ranging from 0.09 to 0.22). The heritability estimates for the production efficiency traits, namely MCI and MSC, were 0.35±0.12 and 0.15±0.09, respectively. The breeding values for production efficiency traits ranged from 0.46 kg/day for MCI to 0.63 kg/day for MSC. A significant and positive genetic correlation between additive and maternal effects was identified, ranging from 0.41 to 0.98. This suggests a consistent and strong interaction between genetic factors inherited from the dam. Rank correlation of breeding values across all six models ranged from 0.71 (non-significant) to 1.00 for MCI and MSC. MCI exhibited positive genetic and phenotypic trends, showing annual increases of 0.009±0.005 kg/day and 0.148±0.018 kg/day, respectively. In contrast, MSC displayed a very low negative genetic trend (-0.001±0.001 kg/day), while a positive phenotypic trend was observed at 0.047±0.006 kg/day per year. These trends indicate that both selection and management practices are concurrently contributing to the improvement of production efficiency traits.